Welcome to Westonci.ca, your go-to destination for finding answers to all your questions. Join our expert community today! Our Q&A platform provides quick and trustworthy answers to your questions from experienced professionals in different areas of expertise. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
To solve the problem, we need to understand and apply two transformations to the linear parent function [tex]\( f(x) = x \)[/tex]:
1. Vertically stretching the function by a factor of 14.
2. Flipping the function over the [tex]\( x \)[/tex]-axis.
Let's proceed step-by-step:
### Step 1: Vertically Stretch by a Factor of 14
When we vertically stretch a function [tex]\( f(x) \)[/tex] by a factor of 14, each [tex]\( y \)[/tex]-value of the function gets multiplied by 14. Therefore, the transformed function [tex]\( f'(x) \)[/tex] will be:
[tex]\[ f'(x) = 14 \cdot f(x) = 14 \cdot x \][/tex]
Now, our function has been transformed into:
[tex]\[ f'(x) = 14x \][/tex]
### Step 2: Flip Over the [tex]\( x \)[/tex]-Axis
When we flip a function over the [tex]\( x \)[/tex]-axis, we multiply the entire function by -1. Therefore, applying this transformation to [tex]\( f'(x) = 14x \)[/tex], we get the new function [tex]\( g(x) \)[/tex]:
[tex]\[ g(x) = -1 \cdot 14x = -14x \][/tex]
So, the final equation of the new function after applying both transformations is:
[tex]\[ g(x) = -14x \][/tex]
### Conclusion
Among the given choices:
- A. [tex]\( g(x) = 14x - 1 \)[/tex]
- B. [tex]\( g(x) = -\frac{1}{14}x \)[/tex]
- C. [tex]\( g(x) = -14x \)[/tex]
- D. [tex]\( g(x) = \frac{14}{x} \)[/tex]
The correct answer is:
C. [tex]\( g(x) = -14x \)[/tex]
1. Vertically stretching the function by a factor of 14.
2. Flipping the function over the [tex]\( x \)[/tex]-axis.
Let's proceed step-by-step:
### Step 1: Vertically Stretch by a Factor of 14
When we vertically stretch a function [tex]\( f(x) \)[/tex] by a factor of 14, each [tex]\( y \)[/tex]-value of the function gets multiplied by 14. Therefore, the transformed function [tex]\( f'(x) \)[/tex] will be:
[tex]\[ f'(x) = 14 \cdot f(x) = 14 \cdot x \][/tex]
Now, our function has been transformed into:
[tex]\[ f'(x) = 14x \][/tex]
### Step 2: Flip Over the [tex]\( x \)[/tex]-Axis
When we flip a function over the [tex]\( x \)[/tex]-axis, we multiply the entire function by -1. Therefore, applying this transformation to [tex]\( f'(x) = 14x \)[/tex], we get the new function [tex]\( g(x) \)[/tex]:
[tex]\[ g(x) = -1 \cdot 14x = -14x \][/tex]
So, the final equation of the new function after applying both transformations is:
[tex]\[ g(x) = -14x \][/tex]
### Conclusion
Among the given choices:
- A. [tex]\( g(x) = 14x - 1 \)[/tex]
- B. [tex]\( g(x) = -\frac{1}{14}x \)[/tex]
- C. [tex]\( g(x) = -14x \)[/tex]
- D. [tex]\( g(x) = \frac{14}{x} \)[/tex]
The correct answer is:
C. [tex]\( g(x) = -14x \)[/tex]
Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.